Biomimetic Scaffold Design for Functional and Integrative Tendon Repair - Zhang, Xinzhi (2012)
Rotator cuff tears represent the most common shoulder injuries in the United States. The debilitating effect of this degenerative condition coupled with the high incidence of failure associated with existing graft choices underscore the clinical need for alternative grafting solutions. The two critical design criteria for the ideal tendon graft would require the graft to not only exhibit physiologically relevant mechanical properties but also be able to facilitate functional graft integration by promoting the regeneration of the native tendon-to-bone interface. Centered on these design goals, this review will highlight current approaches to functional and integrative tendon repair. In particular, the application of biomimetic design principles through the use of nanofiber- and nanocomposite-based scaffolds for tendon tissue engineering will be discussed. This review will begin with nanofiber-based approaches to functional tendon repair, followed by a section highlighting the exciting research on tendon-to-bone interface regeneration, with an emphasis on implementation of strategic biomimicry in nanofiber scaffold design and the concomitant formation of graded multi-tissue systems for integrative soft tissue repair. This review will conclude with a summary and future directions section.